Prevention, communication and equity in environmental epidemiology: ethical issues - Giordana Pagliarani; Caterina Botti (Istituto Superiore di Sanità, 2011)
In environmental epidemiology research, decisions about when and how to intervene requires adequate ethical reflection. In fact, different kinds of issues may arise about: research methods and knowledge production; management of the results in terms of their overall assessments or for the implementation of preventive actions; reclamation intervention. In this contribution we propose to consider three topics we regard as crucial to this ethical debate: the reporting of conclusive research data; the correct application of the precautionary principle; and the environmental equity issues.